An Overview of Orthodontic Patients Visiting in a Tertiary Care Hospital in Northern Region of Bangladesh (KYAMC Journal, 2021)
Background: Malocclusion is still not considered as a dental problem because of more emphasis is given to the treatment of dental caries and periodontal diseases due to pain complained by patients.Objective: The study was conducted to find out the pattern of diseases of orthodontic patients visiting in a regional tertiary care hospital in northern area of Bangladesh.Materials and Methods: This snap-shot study was conducted on randomly selected 84 patients attended in the Department of Orthodontics & Dentofacial Orthopaedics, Dental unit Thengamara Mohila Sabuj Sangha (TMSS) Medical College and Hospital, Bogura from July 2016 to June 2017. All data were collected from patients’ history and clinical examination of the patients. Descriptive statistics were calculated using MS Excel from the collected data.Results: One third of the patients (33.33%) have normal over bite. Class I and Class II molar relationship are distributed as 44% and 53.5% respectively. Class I and Class II division 1 Incisor relationship is distributed as near about same, 44% and 34.52% respectively; and 14.29% have Class II division 2. Class I and Class II Canine relationship are distributed as near about same, 44% and 48.80% respectively. Forty four percent patients have normal over jet, 34.52% patients have increased over jet, and 7.20% patients have reversed over jet.Conclusion: The epidemiological data on the prevalence of malocclusion is an important determinant in planning appropriate levels of orthodontic services in the Bangladeshi population and further studies are required to provide accurate estimates of the orthodontic treatment.KYAMC Journal.2021;12(02): 92-97